Olimpíadas escolares no Espírito Santo : continuidades e descontinuidades (1946-1954) - Eller, Marcelo Laquini (2015)
Addresses the development of the School Olympics in the Espírito Santo in the period between 1946 and 1954. It aims at understanding the continuities and discontinuities of this sport phenomenon and the relationship between the new example of student competitions and sports culture capixaba. The theoretical and methodological framework for the construction of historical narrative, as Carlo Ginzburg used authors, Jacques Le Goff, Marc Bloch, Norbert Elias and Roberto Da Mata. As sources we make use of capixaba press, materialized in major newspapers run on time, the special file Aloyr Queiroz de Araújo, the magazine Vida Capichaba, as well as interviews with actors involved in the School Games. The School Olympiad was organized by the Physical Education Service (SEF), State government agency linked to the Ministry of Public Instruction, having as its creator Professor Aloyr Queiroz de Araújo. The student competitions were held twice a year, in the capital, as in the state following coubertianos patterns, usually held on holidays demonstrating their civic and patriotic character. Regarding the education of Physical Education in the State of the Espírito Santo, we note that the Physical Education Service (SEF), a body created by the government to control and direct the actions of Physical Education in state secondary schools had a decisive role in this context to enable and form for the labor market teachers and monitors the area. At first, the discontinuity can be seen when school games are transformed by the State School Games, proposing new meanings to these practices, similar to those called coubertianos. The second discontinuity occurs for financial reasons, when the state decides to abandon the pedagogical project of the School Olympics and back their energies less to the city and more to the field.